Sense of Identity Among Elderly People on the Example of the Southern Part of Polish - Czech Borderline - Katarzyna Zofia Jas (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Identity is created throughout the whole life of a person, however, after sixties self-perceptions undergoes significant metamorphosis. At the stage of development, a human being searches for contacts with another person, finds aspects in common, things which may connect, and uniqueness and otherness of a person are moved to the background. The research and deliberating about the issue of identity creation are based on distinguishing aspects whichare identical and those which are different. The study is a statement of a research conducted in Cieszyn and Czech Cieszyn - the southern part of Polish - Czech borderline. Quantity and quality strategies were used as complimentary ones. The aim of deliberating was to know the sense of identity among people in their late adulthood who reside Polish and Czech parts of Cieszyn Silesia. The results of research conducted allow to notice similarities and differences in sense of identity declarations amongpeople in their late adulthood who live in Cieszyn and Czech Cieszyn. Identity creation is a long-term process, time-consuming, contemplative, with elements of inner retrospection. People in their late adulthood develop their sense of identity against the background of differenced which are noticed in their childhood, adolescence, youth, and adulthood.